التحليل الجغرافي لبعض مؤشرات التنمية البشرية في ليبيا من 2010 – 2023 (Comprehensive Journal of Science, 2025)
This study aimed to analyze demographic, social, economic, and health indicators in Libya during the period 2010-2023, evaluate the distribution of people with disabilities and its impact on social and health services, and investigate the prevalence of malnutrition and anemia among vulnerable groups. The study employed a descriptive analytical approach, collecting and analyzing secondary data from national surveys and official reports. The findings revealed a notable increase in population, a rise in the number of people with disabilities, and disparities in malnutrition and anemia rates across regions. The study recommended intensifying awareness campaigns, improving infrastructure, supporting healthy food distribution programs, and providing comprehensive rehabilitation services for people with disabilities. It also suggested developing special nutritional and health programs for pregnant women, expanding basic health services, and investing in education and vocational training for youth. The proposals included providing specialized medical teams, expanding social and health care services, raising health and nutritional awareness, and providing nutritional supplements for women of childbearing age